Changes in forage quality of an upland permanent grassland under climate change including a summer extreme drought combined with a heat wave - Niderkorn V.; Ginane C.; Dumont B.; Andueza D.; Le Morvan A.; Decaux M.L.; Morvan-Bertrand A.; Picon-Cochard C. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
An experiment was conducted to predict the response of an upland permanent grassland to future climate change including a summer extreme event. Treatments combined current and future atmospheric CO2 concentrations (380 and 520 ppm, respectively) with or without an extreme event consisting of a twoweek heat wave (+6°C) associated with severe drought during the three summer months, followed by a recovery period in autumn. During the experiment, air temperature was regulated 2°C above the current temperature for all four treatments. Forage quality was measured four times: once in spring the year before the extreme climatic event, twice in spring just before the extreme event, and once in autumn when plants have been rehydrated after the event. Elevated CO2 resulted in a decrease in plant nitrogen (N) and cell wall contents (NDF), while the extreme event increased N and decreased NDF. Changes in plant chemical composition impacted rumen fermentation as the extreme event consistently increased in vitro dry matter digestibility. Extreme climatic events may thus be most likely to modify plant tissue chemistry and improve forage quality than changes in atmospheric CO2 concentration.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)